Neurology of the cryopyrin‐associated periodic fever syndrome. (2nd March 2016) - Parker, T.; Keddie, S.; Kidd, D.; Lane, T.; Maviki, M.; Hawkins, P. N.; Lachmann, H. J.; Ginsberg, L.
Abstract : Background and purpose: The cryopyrin‐associated periodic fever syndrome (CAPS) is an autosomal dominant autoinflammatory disorder caused by mutations in the NLRP3 gene and is typified by recurrent episodes of systemic inflammation resulting in fever, urticarial rash and arthralgia. In addition to these systemic aspects, CAPS has multiple neurological manifestations. The largest case series to date is presented focusing on the neurological features of this disorder. Methods: The case histories of a cohort of 38 UK patients with genetically proven CAPS who were treated with interleukin 1β (IL‐1β) inhibition as part of a national treatment programme and underwent detailed neurological assessment were reviewed. Results: Across the entire disease course neurological manifestations were present in 95% of patients; 84% had some form of headache; 66% sensorineural hearing loss; 60% myalgia; 34% papilloedema and 26% optic atrophy. Patients with the T348M mutation tended to have a more severe neurological phenotype with an earlier age of onset. Four patients had cerebrospinal fluid examination, three of whom had evidence of aseptic meningitis. There was a marked response to IL‐1β inhibition, which has revolutionized management of these patients (29/32 patients with headache responding). Conclusion: Neurological symptoms are extremely common in CAPS and these results highlight the importance of increasing awareness amongst neurologists, particularly as highly effective therapies are available. Abstract : Clickhere for the corresponding questions to this CME article.